2015
DOI: 10.1007/s00167-015-3856-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and rehabilitation of paediatric anterior cruciate ligament injuries

Abstract: This file was dowloaded from the institutional repository Brage NIH -brage.bibsys.no/nih Moksnes, H., Grindem, H. (2015

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 75 publications
(104 reference statements)
0
29
0
Order By: Relevance
“…The rate of ACL injuries in children and adolescents does not appear to be uniform across age groups [17]. Data from a pediatric medical center in Boston, United States of America (USA) between 2000 and 2009 showed that ACL injuries account for 6.3% of all sports injuries in 5- to 12-year-olds, but 10.6% in 13- to 17-year-olds [18].…”
Section: Introductionmentioning
confidence: 99%
“…The rate of ACL injuries in children and adolescents does not appear to be uniform across age groups [17]. Data from a pediatric medical center in Boston, United States of America (USA) between 2000 and 2009 showed that ACL injuries account for 6.3% of all sports injuries in 5- to 12-year-olds, but 10.6% in 13- to 17-year-olds [18].…”
Section: Introductionmentioning
confidence: 99%
“…When an NMT program optimized just one of the four key components of a prevention program (younger age, high volume, multiple exercise modes, or feedback), a 17–18% ACL injury risk reduction was observed 39. Moksnes and Grindem reviewed the existing literature on prevention of ACL injury in skeletally immature patients, and although they noted evidence for the effectiveness of prevention programs in girls as young as 12 years old, these findings have not yet been found in younger children 29. Additionally, the ideal timing, frequency, and duration of such interventions in children and adolescents are unknown.…”
Section: Prevention Of Acl Injurymentioning
confidence: 99%
“…As noted in a recent review, rehabilitation following ACL reconstruction in children is not well described 29. Rehabilitation should be supervised, and functional milestones should be used to help guide therapy progression 29.…”
Section: Rehabilitationmentioning
confidence: 99%
See 2 more Smart Citations